Leitura fenomenológica das tecnologias de inforrmação e comunicação em uma escola públlica estadual paulista: descrição fenomenológica do uso e emprego dos computadores na escola - Mainine, Sueli (2008)
The PHENOMENOLOGICAL READING OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN A PUBLIC SCHOOL IN THE STATE OF SP, the purpose of the present study, concerns the relationship between man and the world, especially the student and the computer learning, The strategy is to capture that essence in a phenomenological way regarding the effect caused by the introduction of Information and Communication Technologies (ICT) as educational tools. The investigation was based on the premise that school universe is better understood when the student experiences the Information and Communication Technologies as educational instruments. It is said that Information and communication Technologies favor inclusion, integration and the construction of a more ethical world. Such premise motivated the study of epistemological fundaments that help us understand how students and teachers deal with computers as aid tools in the teaching-learning process, as well as the effects and impressions that come out of that experience. With that in mind, we analyzed the social, economic and cultural context of the present research participants and we focused them in the theory of knowledge under the phenomenological view. The research is based on the work of HUSSERL, E.(1982)1, MERLEAU-PONTY, M.(1973; 1999)2 and other authors who study phenomenological approaches. By investigating what is perceived and expressed, by working with what makes sense to the individuals and by highlighting the students thoughts of themselves and school after the introduction of the computer in the school routine, we have learned some aspects of that phenomenon and have searched for the ideas expressed on the descriptions and speeches of students and teachers. The data analysis has helped articulate the students and the teachers views. By considering the meaningful relations, we have understood the sense and the meaning of events through the phenomenological description. It is concluded that "Projeto Letramento Números em Ação" offers some positive aspects of FREIRE,P. (1997)3 line as it takes into consideration the premises of dialogic treatment to advance on the student s understanding and it proposes digital inclusion, however due to the little continuous attention, it has not brought more meaningful evolvements to the learning process